Simultaneous Estimation of Paracetamol and Aceclofenac in Combined Dosage Forms by RP-HPLC Method - SENTHAMIL SELVAN, P.; GOPINATH, R.; SARAVANAN, V.S.; GOPAL, N.; SARVANA KUMAR, A.; PERIYASAMY, K. (Asian Journal of Chemistry, 2010)
A simple, selective, rapid, precise and economical reversed phase high performance liquid chromatography (RP-HPLC) method has been developed for the simultaneous estimation of paracetamol and aceclofenac from tablets. The method was carried out on a Hichrom C18 (25 cm × 4.6 mm i.d., 5 μ) column with a mobile phase consisting of acetonitrile: 20 mM phosphate buffer (adjusted to pH 5.0 using orthophosphoric acid) (60 : 40 v/v) at a flow rate of 0.8 mL/min. Detection was carried out at 265 nm. Etoricoxib was used as internal standard. The retention time of paracetamol, aceclofenac and etoricoxib were 4.75, 6.44 and 8.83 min, respectively. The validation of the proposed method was also carried out according to ICH guidelines. The proposed method can be used for the estimation of these drugs in combined dosage forms.